Eosinophil count and treatment response in COPD patients - CR Kiran; K Anitha Kumari; Sanjeev Nair; A Fathahudeen (Lung India)
Background and Objective: Eosinophils are an integral part of lung defence against microbes. It is also responsible for untoward hyper immune responses responsible for lung diseases including Chronic Obstructive Pulmonary Disease (COPD). To compare COPD patients with high and low Absolute Eosinophil Count (AEC) regarding their frequency of exacerbations, and response to treatment. Materials and Methods: Prospective observational study. Patients were divided into 2 groups above and below the mean AEC and followed up for 6 months, during when their frequencies of exacerbations were followed up. At the end of 6 months, symptomatology and lung function were reassessed. Results: Those with high AEC had a shorter time to first exacerbation. These patients also needed significantly greater number of inpatient admissions during the study period. Fall in FEV1 was also significantly higher in this group. There was no significant difference in changes in BMI, CAT or MMRC scores, between these groups. Conclusion: Patients with high AEC are at higher risk of exacerbations, as well as loss of lung function.